Ultrathin ZnIn2S4 Nanosheets Anchored on Ti3C2TX MXene for Photocatalytic H2 Evolution. (7th May 2020) - Zuo, Gancheng; Wang, Yuting; Teo, Wei Liang; Xie, Aming; Guo, Yang; Dai, Yuxuan; Zhou, Weiqiang; Jana, Deblin; Xian, Qiming; Dong, Wei; Zhao, Yanli
Abstract: Photocatalysts derived from semiconductor heterojunctions that harvest solar energy and catalyze reactions still suffer from low solar‐to‐hydrogen conversion efficiency. Now, MXene (Ti3 C2 TX ) nanosheets (MNs) are used to support the in situ growth of ultrathin ZnIn2 S4 nanosheets (UZNs), producing sandwich‐like hierarchical heterostructures (UZNs‐MNs‐UZNs) for efficient photocatalytic H2 evolution. Opportune lateral epitaxy of UZNs on the surface of MNs improves specific surface area, pore diameter, and hydrophilicity of the resulting materials, all of which could be beneficial to the photocatalytic activity. Owing to the Schottky junction and ultrathin 2D structures of UZNs and MNs, the heterostructures could effectively suppress photoexcited electron–hole recombination and boost photoexcited charge transfer and separation. The heterostructure photocatalyst exhibits improved photocatalytic H2 evolution performance (6.6 times higher than pristine ZnIn2 S4 ) and excellent stability. Abstract : MXene nanosheets are used to support the in situ growth of ultrathin ZnIn2 S4 . The obtained sandwich‐like hierarchical heterostructure could effectively suppress photoexcited electron–hole recombination and boost photoexcited charge transfer and separation, exhibiting efficient photocatalytic H2 evolution performance and excellent stability.